Daily-life stress reactivity and recovery following virtual-reality-based cognitive behavioral therapy in patients with a psychotic disorder - van der Stouwe, Elisabeth C. D.; Booij, Sanne H.; Geraets, Chris N. W.; Pot-Kolder, Roos M. C. A.; Kuranova, Anna; van der Gaag, Mark; Veling, Wim (Frontiers in Psychiatry, 2024)
Studies have consistently demonstrated increased stress sensitivity in individuals with psychosis.Since stress sensitivity may play a role in the onset and maintenance of psychosis, this could potentially be a promising target for treatment. The current study was the first to investigate whether reactivity to and recovery from daily-life stressors in psychosis change in response to treatment, namely virtual-reality-based cognitive behavioural therapy (VR-CBT).116 patients were randomized to either VR-CBT or the waiting list control group (WL). Pre-treatment and post-treatment participants completed a diary ten times a day during six to ten days. Multilevel analyses were used to model the time-lagged effects of daily stressful events on negative affect (NA) and paranoia symptoms to examine reactivity and recovery.There was a significant difference in NA reactivity. VR-CBT showed higher NA at post-treatment compared to pre-treatment than WL (bpre=0.14; bpost=0.19 vs bpre=0.18; bpost=0.14). There was a significant difference in NA recovery and paranoia recovery between the groups at lag 1: VR-CBT showed relatively lower negative affect (bpre=0.07; bpost=-0.06) and paranoia (bpre= 0.08; bpost=-0.10) at post-treatment compared to pre-treatment than WL (bpre=0.08; bpost=0.08; bpre=0.04; bpost=0.03).Negative affect and paranoia recovery improved in response to treatment. Increased NA reactivity may be explained by a decrease in safety behaviour in the VR-CBT group. The discrepancy between reactivity and recovery findings may be explained by the inhibitory learning theory that suggests that an original threat reaction may not erase but can be inhibited as a consequence of exposure therapy.